2014
DOI: 10.1063/1.4895792
|View full text |Cite
|
Sign up to set email alerts
|

Excitation energies from particle-particle random phase approximation: Davidson algorithm and benchmark studies

Abstract: The particle-particle random phase approximation (pp-RPA) has been used to investigate excitation problems in our recent paper [Y. Yang, H. van Aggelen, and W. Yang, J. Chem. Phys. 139, 224105 (2013)]. It has been shown to be capable of describing double, Rydberg, and charge transfer excitations, which are challenging for conventional time-dependent density functional theory (TDDFT). However, its performance on larger molecules is unknown as a result of its expensive O(N(6)) scaling. In this article, we derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
94
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(98 citation statements)
references
References 33 publications
(50 reference statements)
4
94
0
Order By: Relevance
“…In Refs. 7 and 30 such behavior was observed as well, that is, large underestimation of triplet excitation energies upon inclusion of large amount of exact exchange or by using the RPA method, respectively. In Table also these five states have been excluded from the RPA and RPA(D) results leaving 50 states which seem to behave normally and which results in statistical measures comparable to those of the singlet excited states.…”
Section: Benchmark Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…In Refs. 7 and 30 such behavior was observed as well, that is, large underestimation of triplet excitation energies upon inclusion of large amount of exact exchange or by using the RPA method, respectively. In Table also these five states have been excluded from the RPA and RPA(D) results leaving 50 states which seem to behave normally and which results in statistical measures comparable to those of the singlet excited states.…”
Section: Benchmark Resultsmentioning
confidence: 74%
“…The same behavior was observed in the TDDFT study from Peach et al upon inclusion of a large amount of exact (Hartree–Fock) exchange in DFT hybrid functionals for the 1 3 B u state of butadiene, the 1 3 B 1 u state of benzoquinone as well as the 1 3 B 2 u state of naphthalene. In a recent study by Yang et al, another seven imaginary triplet RPA excitation energies were reported. In addition to the 10 previously reported unstable RPA states, we observed another six imaginary excitation energies.…”
Section: Benchmark Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In practice, even though it intrinsically misses non-HOMO excitations, the pp-RPA has been demonstrated to be able to solve such greatly challenging problems as double excitations, Rydberg excitations, charge-transfer excitations, ST gaps for diradical systems, as well as regular HOMO-dominated single excitations (81,83,85,86). According to the benchmark studies (83,85), the Becke-3-Lee-Yang-Parr (B3LYP) functional generally provides an N−2 reference that gives rise to reliable pp-RPA excitation energies and has fewer convergence difficulties. In contrast, the HF functional often yields larger error whereas the Perdew-Burke-Ernzerhof functional frequently encounters N−2 convergence problems.…”
Section: Significancementioning
confidence: 99%
“…It was later further extended to describing excitations (81)(82)(83)(84). For excited states calculation, it starts from a two-electron deficient (N−2) system described with DFT correlation, then recovers a series of neutral states by adding back two explicitly correlated electrons.…”
Section: Significancementioning
confidence: 99%